Creating an Education Research Acculturation Theory for Research Implementation in School. (July 2013) - Chua, Yan Piaw; Tie, Fatt Hee; Don, Zuraidah Mohd
This study investigates the implementation of educational research among urban secondary schools in Malaysia. The respondents include school teachers and administrators, lecturers in education institutions, and committee members of the state education departments. Data collected from interviews were coded and analyzed using open, axial and selected coding procedures. Six core categories emerged from the data namely implementation initiative, implementation obstacles, collaboration, research knowledge, research needs, and suggestions to overcome the weaknesses. The findings showed that the quality and quantity of education research in school depend on the existence of a research culture. The findings of this study form an education research acculturation theory for research implementation in schools.